(untitled) (Bangladesh Journal of Agricultural Research, 2018)
The study was conducted to evaluate the effect of botanicals namely neem leaf extract, neem oil, mahogany oil, mahogany oil + mahogany cake, garlic extract, tobacco leaf extract along with an untreated control to manage brinjal shoot and fruit borer (BSFB). The percent shoot infestation reduction over control was the highest in mahogany oil + mahogany cake treated plot resulting 62.39%, 64.44%, 67.86% and 71.05% reduction at vegetative stage and early, mid and late fruiting stage, respectively. The same treatment provided the highest fruit infestation reduction over control resulting 86.70%, 85.08% and 85.50% reduction at early, mid and late fruiting stage, respectively. The lowest number of larvae per infested shoot was recorded 1.10 and 1.08 in the same treatment at early and mid fruiting stage, respectively but notat vegetative stage and late fruiting stages. The number of larvae per infested fruit was similarly lowest having 1.50, 1.06 and 1.07 at early, mid and late fruiting stage, respectively using the same approach. The maximum yield (35.82 t ha-1) was achieved in the mahogany oil + mahogany cake treated plot with the highest benefit cost ratio (2.35). Bangladesh J. Agril. Res. 43(3): 431-440, September 2018